Overcoming the Ave/Eva Anagrammatic Dichotomy in Postwar Feminist Revisionist Mythology - Cacciola, Anna (Amaltea. Revista de Mitocrítica, 2019)
The revisionist treatment of classical mythology carried out by contemporary poets obeys to demystifying strategies of feminine stereotypes transmitted by patriarchal society, aimed at reconstructing a new symbolic order from the woman’s self-consciousness. However, the antecedents of this process are fixed in the lyrical experimentation carried out by the authors of the immediate postwar period who, taking advantage of the recourse to a biblical imagery, typical of certain religious poetry of the forties, approach the ancient dichotomy Eva / Maria, in order to get away from the figurative conventions associated with these figures and modify the representation of the female collective.